The Effect of Social Support and Religiosity Against Bereavement - Kainama, Jhon Victor; Riasnugrahani, Missiliani; Rohinsa, Meilani (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Bereavement has an impact on reducing a person's psychological capacity and also physical and various roles in life that are lived as a result of the death of a loved one. This study aimed to determine the effect of social support of the congregation and religiosity on bereavement. Respondents were 121 people aged 15 to 85 years, with an average high school education level and had experienced bereavement during the last 18 months. The research data were collected with the Bereavement Experience Questionnaire (BEQ-24), Social support, and The Centrality of Religiosity Scale (CRS-15), with a purposive sampling technique and processed in multiple linear regression using SPSS v.25 application. The coefficient of each scale is 0.91, 0.86, 0.75. From the results of regression-Model 3, it was found that social support provided by the congregation did not have a significant effect on bereavement. While religiosity as an internal resource in bereaves has a significant positive effect on bereavement. The age factor and education level of respondents in this study also contributed to the effect on bereavement.